Sample dimensional reading tests for third year high school - Caporal, Elizabeth Mendoza 1924- (1975)
This research paper presents sample dimensional reading tests to determine a third year student's ability to comprehend reading materials and to appraise the level of complexity which he can understand with different degrees of thoroughness of detail.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Reading (Secondary education).; Reading readiness